Revisiting the Historical Challenges of Islamic Da’wah in South Korea A Comparative Religious Analysis - Mohd Ghazi, Ahmad Faris Naqiyuddin; Mohamad Jamil, Asyiqah; Fathil, Fauziah; Karaman, Mert Sabri (Human Sustainability Procedia, 2025)
This article critically examines the historical trajectory and contemporary challenges of Islamic Da’wah in South Korea, a country characterized by unique religious pluralism and cultural syncretism. Despite early contacts with Muslim traders during the Goryeo Dynasty (918-1392) and later exposure through the Turkish military during the Korean War (1950 - 1953), Islam has remained a minority faith in South Korea. The study aims to investigate the socio-religious factors that have contributed to Islam’s limited penetration by conducting a qualitative historical analysis based on secondary data. Drawing upon academic publications, historical records, and sociological studies, this paper systematically analyses South Korea’s dominant religious systems such as Shamanism, Buddhism, Confucianism and Christianity related to their interaction with Islamic teachings. The findings reveal that the entrenched cultural heritage, historical Confucian governance, syncretic religious attitudes and the proactive expansion of Christianity have collectively shaped a challenging environment for Islamic da’wah in South Korea. The paper concludes by arguing that future Islamic outreach must strategically balance cultural engagement with doctrinal authenticity in order to navigate South Korea’s complex socio-religious landscape. This study contributes to the growing field of religious studies by offering an underexplored case study of Islam’s marginalization in East Asian society.